HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN KEAKTIFAN PESERTA POSYANDU LANSIA MENGIKUTI POSYANDU LANSIA DESA SUDIMARA DAN DESA GUBUG KABUPATEN TABANAN 2019 - Saadah, Nur; Lubis, Dinar Saurmauli (ARCHIVE OF COMMUNITY HEALTH, 2019)
ABSTRACT Improving the health status of the elderly is an important thing that must be done by the government. One effort to improve the health status of the elderly is posyandu for the elderly. The behavior of the elderly posyandu participants visiting health services is determined by three factors. Among the three factors, the factor of family support is very important because it is a reinforcing factor of a person's behavior. Therefore, this study aims to determine the relationship between family support and the active participation of elderly posyandu participants in the elderly posyandu in Sudimara and Gubug Tabanan regency 2019. The dependent variable of this study was family support consisting of sub-variables emotional support, award support, instrumental support , informational support. The independent variable of this research is the activity of the elderly posyandu participants. The design of this study uses cross-sectional. The population is all the elderly recorded in 2 villages, namely Sudimara Village and Gubug Village totaling 113 elderly. Data were analyzed by chi square test and processed using computer software. Respondents received good support from their families emotionally and appreciation, instrumental, and also informational support. Respondents in this study actively participated in the elderly posyandu activities as many as 73 respondents (64.6%). The relationship of family support in general did not have a statistical effect on the activity of elderly posyandu participants (p = 0.319; 95% CI OR = 0.683-3.215; OR = 1.48). Keywords : Family Support, Emotional, Instrumental, Informational, Elderly.